2011
DOI: 10.1007/s10705-011-9454-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of recycled P products as P fertilizers, as evaluated in pot experiments

Abstract: World phosphorus (P) resources are limited and may be exhausted within 70-175 years. Therefore recycling of P from waste materials by chemical or thermal processes is important. This study evaluated the effectiveness of recycled P products from sewage sludge and animal wastes as P fertilizer. Four products were obtained from chemical processes, three magnesium-ammoniumphosphates (MAP) of different sewage treatment plants and a Ca phosphate precipitated from wastewater (Ca-P) and four from thermal processes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
125
7
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(151 citation statements)
references
References 27 publications
(24 reference statements)
10
125
7
3
Order By: Relevance
“…Previous studies comparing P fertilizers/struvites recovered from various materials to commercial P fertilizer have reported that the recycled products increased DMY in maize [20], led to comparable DMY in perennial ryegrass [22], or at least improved DMY compared to untreated controls in several crops [17][18][19]43].…”
Section: The Fertilizing Performance Of P-salt Is Equivalent To That mentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies comparing P fertilizers/struvites recovered from various materials to commercial P fertilizer have reported that the recycled products increased DMY in maize [20], led to comparable DMY in perennial ryegrass [22], or at least improved DMY compared to untreated controls in several crops [17][18][19]43].…”
Section: The Fertilizing Performance Of P-salt Is Equivalent To That mentioning
confidence: 97%
“…Several studies have found that struvite recovered from different materials can improve the yields of various crops compared to untreated controls [17][18][19]. Struvite recovered from swine wastewater has been shown to increase the biomass yield of maize more than commercial P fertilizer [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous investigations have also suggested that struvite may be an effective fertilizer for acidic soil. 8,20 Massey et al 10 conducted a greenhouse study with struvite and other P fertilizers at different soil pH levels and reported that struvite was effective at both acidic and slightly alkaline pH levels. However, it was found in our study that struvite in cinnamon soil (pH 7.3) had lower performance on biomass compared to CSP treatment, but not significantly, but showed significantly higher level in biomass in paddy soil (pH 5.3).…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…It is known that water-soluble P fertilizer is generally considered to be fully plant available, and the P uptake from struvite has been studied in the greenhouse with a variety of test plants on soils compared with commercial P fertilizer. [8][9][10][11] evaluated the availability of urine-derived struvite as fertilizer and found that struvite led to biomass yield and P uptake comparable to or higher than those induced by a commercial mineral fertilizer. A few reports of the comparison of soils with different pH values can be found in previous research.…”
Section: ■ Introductionmentioning
confidence: 99%